A SPICE Compatible Model of Graphene/Silicon Schottky Barrier Photodiode. (7th July 2017) - Srivastava, Ashok; Chen, Xinlu; Pradhan, Aswini K
Abstract : In this work, a theoretical analysis is presented for the photo-response studies of graphene/silicon Schottky barrier type diodes. A computed 238.8 W -1 photocurrent to dark current ratio normalized by the power source (633nm wavelength and 10mW laser) is obtained. An equivalent circuit model of the graphene/silicon Schottky barrier diode compatible with SPICE simulation is developed and simulated photo-response characteristics are presented using analog behavior modeling which are in close agreement with the theoretical analysis.